Measuring the image of Malaysia as a tourist destination - Mahadzirah, Mohamad; Nur Izzati, Ab. Ghani; Abdul Manan, Ali; Ahmad Rusdi, Abdullah (2013)
The study of destination image is essential as it can affect the demand towards a destination. However, according to the World Travel and Tourism Council (WTTC), Malaysia is reported to have failed in positioning its image as a tourist destination in the minds of tourists. In view of this, the objective of this study is to investigate the underlying factors that measure the destination image of Malaysia. This study is important to address the issue of changing Malaysia’s destination image. Ascertaining Malaysia’s destination image from the perceptions of tourists would be helpful in revealing the right image of Malaysia so that Malaysian Tourism Board (Tourism Malaysia) can effectively promote the image to encourage tourists to choose Malaysia as their choice of travel destination. Data for this study was obtained through a survey questionnaire. Data collection was conducted at Kuala Lumpur International Airport (KLIA). The usable sample size was 261 European tourists visiting Malaysia. The exploratory and confirmatory factor analyses were used to conduct data analysis. In addition, the goodness-of-fit of the measurement model was also determined. The findings revealed that it is important for the Tourism Malaysia to portray Malaysia as a natured-based travel destination, which offers an adventurous holiday with the chance to see wildlife and relaxing on nice beaches among European tourists since the country is blessed with abundant natural resource.